School choice or the politics of desperation? Black and Latinx parents of students with dis/abilities selecting charter schools in Chicago - Waitoller, Federico R.; Super, Gia (Education Policy Analysis Archives, 2017)
In this paper, we focus on the city of Chicago to examine how Black and Latinx parents of students with dis/abilities engage with school choice. Using analytical tools from grounded theory (Strauss & Corbin, 1990) and a theoretical lens informed by critical notions of space, race and dis/ability, we analyze interviews with parents of students with dis/abilities, field notes, and various artifacts from charter schools (e.g., student handbooks and websites). We found that parents engaged with the politics of desperation (Stovall, 2013): an assemblage of thoughts and rationales to make school decisions amid poor and ableist educational options for Black and Latinx students with dis/abilities. We found that the neoliberal restructuring of urban education space was a driving force shaping parents’ engagement with the politics of desperation. Thus, our study sheds light on the relationship between race, dis/ability, and urban spatial restructuring.